STRATEGI PENGELOLAAN LIMBAH PADAT DALAM MENDUKUNG KEBERLANJUTAN GREEN CAMPUS: SEBUAH PENDEKATAN AHP - Dino Rimantho; Nur Yulianti Hidayah; Ayu Herzanita; Anggina Sandi (Universitas Lambung Mangkurat, 2022)
The purpose of this study is to find the most sustainable solid waste management scenario for universities. It is based on the Green Campus concept which aims to eliminate waste inefficiencies and use energy sources for ordinary electricity needs, as well as proper disposal management and efficient recycling programs. The Analytic Hierarchy Process approach is used in this study to produce strategic decisions in solid waste management. A pairwise comparison questionnaire was distributed to four experts from universities to give an assessment of the questionnaire. The results show that the alternative of recycling technology innovation is the choice of experts with a weight of 0.429 which is based on technology criteria with a weight of 0.477 and the sub-criteria of Perception and participation of campus residents with a weight of 0.509. Furthermore, the overall assessment of the experts has a consistency value below 0.1. This research could be a starting point in developing a Green Campus sustainability strategy through solid waste management.